THE FACTORS THAT SUPPORT AND IMPEDE ACADEMIC ENTREPRENEURSHIP IN BIOTECHNOLOGY - Roberts, Michelle (My University, 2011)
Academic entrepreneurship in biotechnology is a potential source of economic growth and human development for South Africa. The research undertaken here sought to investigate the factors that support or impede such entrepreneurs in South Africa. This research work is a qualitative study aimed at eliciting the perspectives and insights of academic scientists and other key stakeholders in the biotechnology sphere. Twenty-two participants from academia, government and the private sector were interviewed using a structured research tool. The results suggest that a large number of factors currently act as impediments to the academic entrepreneur while only a few are supportive. It is therefore logical to conclude that the challenge for the academic entrepreneur in biotechnology will involve strategising to remove or neutralise these barriers to profitable development. The key to unlocking the potential of academic entrepreneurship is the development of a solid relationship platform between different stakeholders. When such a platform is in place, factors identified as impediments can more easily be solved. The primary factors supporting academic entrepreneurship in biotechnology are the strategy followed by government and the extent of integration of the South African researchers into the global research network. Key factors that appear not to be supportive include the contrasting cognition and behaviour of academic entrepreneurs versus typical entrepreneurs; financial barriers to commercialisation; business skills, knowledge, experience and institutional support; societal factors; the compilation and internal dynamics of an entrepreneurial team; existing incentives to venture into academic entrepreneurship; university leadership; collaboration between government, academia and industry and lack of an effective strategy for internationalisation by academic entrepreneurs in biotechnology
MBA - WBS
Keywords: Entrepreneurship; Biotechnology